2009
DOI: 10.1523/jneurosci.2497-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

The Conserved Ig Superfamily Member Turtle Mediates Axonal Tiling in Drosophila

Abstract: Restriction of adjacent same-type axons/dendrites to separate single columns for specific neuronal connections is commonly observed in vertebrates and invertebrates, and is necessary for proper processing of sensory information. Columnar restriction is conceptually similar to tiling, a phenomenon referring to the avoidance of neurites from adjacent same-type neurons. The molecular mechanism underlying the establishment of columnar restriction or axonal/dendritic tiling remains largely undefined. Here, we ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 34 publications
1
40
0
Order By: Relevance
“…Diverse mechanisms restrict these projections, including autocrine suppression of growth cone motility (R7) (Ting et al 2007), repulsive interactions between cells of the same class in adjacent columns (Millard et al 2007; Ferguson et al, 2009), and adhesive interactions between different classes of cells in the same column (Nern et al 2008). As genetic tools become available for analyzing additional classes of neurons that synapse in the medulla, a more complete picture of the cellular dynamics leading to circuit assembly will emerge.…”
Section: Self-assembly Of Laminaementioning
confidence: 99%
“…Diverse mechanisms restrict these projections, including autocrine suppression of growth cone motility (R7) (Ting et al 2007), repulsive interactions between cells of the same class in adjacent columns (Millard et al 2007; Ferguson et al, 2009), and adhesive interactions between different classes of cells in the same column (Nern et al 2008). As genetic tools become available for analyzing additional classes of neurons that synapse in the medulla, a more complete picture of the cellular dynamics leading to circuit assembly will emerge.…”
Section: Self-assembly Of Laminaementioning
confidence: 99%
“…Lessons may be learned from considering similar events in neurons. In the visual system of Drosophila, separate studies showed that homophilic interactions between immunoglobulin superfamily members (Dscam2 and Turtle) mediate tiling between neighboring neurons of the same class (Millard et al, 2007;Ferguson et al, 2009). It would be interesting to investigate whether such molecules or principles of repulsive homophilic interactions regulate the tiling behavior of an altogether different cell type, the OPC.…”
Section: Before Myelination: Opc-opc Interactions Can Regulate Ol Nummentioning
confidence: 99%
“…4). Turtle (Tutl), an IgSF member (see above), is one component of the parallel mutual repulsion pathway (Ferguson et al 2009). Columnar restriction of R7 axons is disrupted, and imp-a3 tiling phenotypes enhanced, by mutations in tutl (Ferguson et al 2009).…”
Section: Wb Grueber and A Sagastimentioning
confidence: 99%
“…Turtle (Tutl), an IgSF member (see above), is one component of the parallel mutual repulsion pathway (Ferguson et al 2009). Columnar restriction of R7 axons is disrupted, and imp-a3 tiling phenotypes enhanced, by mutations in tutl (Ferguson et al 2009). The finding that multiple pathways ensure tiling in this system raises the possibility that in other systems high tiling fidelity may also be an outcome of multiple, partially redundant cues.…”
Section: Wb Grueber and A Sagastimentioning
confidence: 99%